2015
DOI: 10.1007/s10815-015-0543-x
|View full text |Cite
|
Sign up to set email alerts
|

Damage to fetal bovine ovarian tissue caused by cryoprotectant exposure and vitrification is mitigated during tissue culture

Abstract: Purpose The objective of this study is to characterize the impact of exposure to cryoprotectants followed by vitrification on primordial follicle survival and activation using a fetal bovine model. Methods In the first study, fetal bovine cortical pieces were exposed to cryoprotectants with or without sucrose and cultured up to 7 days in the presence or absence of insulin. In the second study, cortical pieces were exposed to cryoprotectants with or without sucrose, vitrified, and cultured up to 7 days after wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…Similar results were obtained after the vitrification of ovarian tissue from bovine (Mouttham, Fortune, & Comizzoli, 2015) and humans (Fabbri et al, 2014). This result suggests that cryoinjuries induced by the SSV method occur mainly in cell membranes and cytoplasmic organelles, thus preserving the nuclear compartment (Sheikhi, Hultenby, Niklasson, Lundqvist, & Hovatta, 2013).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results were obtained after the vitrification of ovarian tissue from bovine (Mouttham, Fortune, & Comizzoli, 2015) and humans (Fabbri et al, 2014). This result suggests that cryoinjuries induced by the SSV method occur mainly in cell membranes and cytoplasmic organelles, thus preserving the nuclear compartment (Sheikhi, Hultenby, Niklasson, Lundqvist, & Hovatta, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…For agoutis, the success of ovarian tissue vitrification was confirmed by the absence of DNA fragmentation in the control group and after SSV process, as determined by the TUNEL technique. Similar results were obtained after the vitrification of ovarian tissue from bovine (Mouttham, Fortune, & Comizzoli, ) and humans (Fabbri et al, ). This result suggests that cryoinjuries induced by the SSV method occur mainly in cell membranes and cytoplasmic organelles, thus preserving the nuclear compartment (Sheikhi, Hultenby, Niklasson, Lundqvist, & Hovatta, ).…”
Section: Discussionsupporting
confidence: 78%
“…(): 39% normal). Furthermore, the current study examined the follicular morphology at multiple time points following tissue warming, which demonstrated that post‐warming ovarian tissue culture is necessary to properly examine the effect of varying vitrification protocols on follicular health (Mouttham et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian tissue vitrification, followed by transplantation, has resulted in the live birth of human babies (Suzuki et al., ). Furthermore, vitrification was been shown to preserve primordial follicle integrity and function (Mouttham, Fortune, & Comizzoli, ), making it an adequate method of primordial follicle cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
“…Cryoprotectants agents have physical and chemical functions in the tissue, altering freezing conditions, in particular, with the formation of ice crystals (Asgari, Valojerdi, Ebrahimi, & Fatehi, 2015) without intoxicating cells in the process (Mouttham, Fortune, & Comizzoli, 2015). Choosing the right CPAs is essential, which should involve prior evaluation of the benefits of the chosen substance including the permeability of the membranes, CPA concentration, the perfect match of cryoprotectant effect and toxicity, the possibility of combination with other CPAs, among others.…”
Section: Introductionmentioning
confidence: 99%